Peningkatan Hasil Belajar Siswa Dengan Model Think Pair Share (TPS) Berbantuan Mystery Pics - Renanda Wahyu Wardana; Lovika Ardana Riswari; Lintang Kironoratri (PGSD Universitas Muria Kudus, 2023)
The research aims to improve student learning outcomes by applying the Think Pair Share model assisted by Mystery Pics for fourth grade students at SD 2 Hadipolo.The research used is classroom action research. This research was conducted in 2 cycles with each cycle consisting of planning, action, observation, and evaluation. This research was conducted at SD 2 Hadipolo. The subjects used were Grade IV SD 2 Hadipolo students for the 2022/2023 academic year, with a total of 19 students, consisting of 13 male students and 6 female students. Data collection techniques carried out in this study include observation and tests. The instrument used to measure learning outcomes in this study is a matter of evaluation. The data in this study were analyzed in a quantitative descriptive manner.The results of this study note that the percentage of students in the skill of writing Pancasila precepts questions is 56% with category D for the qualification of completeness needing guidance. In cycle II there was an increase compared to cycle I in writing Pancasila precept questions by 91% with category B for good thoroughness qualifications.